The liberating role of stand up comedy in exposing socio-political concerns: an analysis of Kate William’s Katepakalypse and Trevor Noah’s That’s racist - Rupapa, Mandoline (Midlands State University, 2014)
This thesis seeks to address the liberative role of stand-up comedy insofar as exposing socio-political issues and injustices. The thesis used qualitative research methodology to gather information. The study also used critical discourse analysis theory which primarily studies the way social power abuse; dominance and inequality are enacted, reproduced and resisted by text and talk in social and political context. Through humour comedians can say anything political sarcastically and evoke laugher to an audience but underneath expose and enlighten the audience on social and political concerns. The research was based on, Trevor Noah s’ That’s Racist and Katt Williams’ Kattpacalypse which were transcribed and served as main data for the analytical part of the study. The analysis highlights themes such as race, governance and bad politics as they are prevalent in most comedies done by the man of colour. In this light, stand-up comedy is depicted as a viable means for social critique as it mocks the audience in a humorous way confronting issues of social importance. In the study it is also established that Trevor Noah and Katt Williams, as comedians, ideally place themselves to scorn the tyranny of political correctness. This is because humour protects them from any persecution when they say politically provocative and sensitive topics. In addition this study also revealed that stand-up comedy is a very potent vehicle in the quest of freedom of expression, thus making the comedian a voice for the voice less communities.